Case Report: Intracranial hemophilic pseudotumor mimicking an aggressive neoplasm: a rare skull-invasive presentation - Regmi, Moksada; Liu, Junyi; Liu, Shikun; Xiong, Ying; Zhao, Zihan; Zhang, Xu; Yang, Chenlong (Frontiers in Surgery, 2026)
Hemophilic pseudotumor is a rare complication of hemophilia in which a chronic, expanding hemorrhagic mass erodes adjacent bone; intracranial presentations are exceedingly uncommon and can mimic neoplasms. We describe a 36-year-old man with severe hemophilia A who developed a five-year, progressively enlarging left frontoparietal swelling with worsening right-sided hemiparesis. MRI demonstrated a heterogeneously enhancing extra-axial lesion destroying the left cranial vault with “mushroom-like” extracranial extension, marked mass effect, and midline shift, initially interpreted as a possible meningioma. Given progressive deficits, the patient underwent resection under intensive factor VIII replacement. Intraoperatively, a 10 × 10 × 5 cm encapsulated lesion containing organizing clot and fibrous tissue was excised en bloc; the skull defect was reconstructed in a staged procedure. Histopathology confirmed hemophilic pseudotumor. Postoperatively, hemiparesis improved markedly; a small epidural hematoma was managed conservatively. At 12 months, MRI showed no recurrence and the patient remained neurologically intact on prophylactic factor VIII. This case highlights the need to include hemophilic pseudotumor in the differential diagnosis of skull lesions in patients with hemophilia and underscores the value of early recognition and multidisciplinary management—particularly meticulous perioperative hemostatic support—to enable safe resection and excellent outcomes.